Development of chromate-free coated steel sheet with high corrosion resistance and conductivity. (2nd September 2016) - Matsuda, T.; Tsuchimoto, K.; Matsuzaki, A.; Croes, K.; Gelling, V. J.
Abstract : The ideal coating structure, which can achieve both high corrosion resistance and high conductivity, was examined by SEM analysis of conventional chromate-free coated steel sheets. Based on the results of SEM analysis, it was found that high conductivity was achieved by maintaining the convex parts of zinc plating crystals at the coating surface. High corrosion resistance was also achieved by combining a novel silicate binder and metal salt. The results of electrochemical analysis revealed that the silicate binder contributed to suppressing the anodic reaction, while a composite coating involving epoxy resin and phosphoric acid was effective for suppressing the cathodic reaction and maintaining a high barrier property for an extended time.